2003
DOI: 10.1002/jnr.10703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the toxic mechanism triggered by Alzheimer's amyloid‐β peptides via p75 neurotrophin receptor in neuronal hybrid cells

Abstract: Neuronal pathology of the brain with Alzheimer's disease (AD) is characterized by numerous depositions of amyloid-beta peptides (Abeta). Abeta binding to the 75-kDa neurotrophin receptor (p75NTR) causes neuronal cell death. Here we report that Abeta causes cell death in neuronal hybrid cells transfected with p75NTR, but not in nontransfected cells, and that p75NTR(L401K) cannot mediate Abeta neurotoxicity. We analyzed the cytotoxic pathway by transfecting pertussis toxin (PTX)-resistant G protein alpha subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 58 publications
6
69
0
1
Order By: Relevance
“…L401K-p75NTR is unable to couple with Go protein. When F11 cells transfected with L401K-p75NTR cDNA were treated with 10 lM Ab(1-42), induction of cell death was not observed, as has been reported earlier (Tsukamoto et al 2003). Likewise, transfection of PLAIDD cDNA followed by treatment of 10 lM Ab(1-42) did not induce cell death at all.…”
Section: Plaidd Enhances Ab Neutrotoxicity Via P75ntrsupporting
confidence: 63%
See 3 more Smart Citations
“…L401K-p75NTR is unable to couple with Go protein. When F11 cells transfected with L401K-p75NTR cDNA were treated with 10 lM Ab(1-42), induction of cell death was not observed, as has been reported earlier (Tsukamoto et al 2003). Likewise, transfection of PLAIDD cDNA followed by treatment of 10 lM Ab(1-42) did not induce cell death at all.…”
Section: Plaidd Enhances Ab Neutrotoxicity Via P75ntrsupporting
confidence: 63%
“…This pathway, mediated by p75NTR, PLAIDD, Gi, JNK, NADPH oxidase, and caspase3-related caspases, is distinct from the pathway by p75NTR, Go, JNK, NADPH oxidase, and caspase3-related caspases that has been elucidated in Ab toxicity mediated by p75NTR (Tsukamoto et al 2003).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…A previous report supports this concept, demonstrating that A␤-derived diffusible ligands (ADDLs) potently alter NGF-mediated signaling in cultured cells [30]. Moreover, several studies suggested that A␤ toxicity is produced through the association with p75NTR [31][32][33][34][35][36][37]. Specifically, A␤ toxicity mediated by p75NTR depends on a death domain [38] in the cytoplasmic part of p75NTR molecules [37].…”
Section: Receptor-mediated A␤ Oligomer Neurotoxicitymentioning
confidence: 75%